Exploring Discovery Learning Applied in English Language Teaching of Higher Education - Nugroho, Andhi Dwi; Karjono, Johanes Climacus Setyo; Hikmah, Isti'anatul; Robiasih, Rr. Hasti; Fiani, Ani (Linguistic, English Education and Art (LEEA) Journal, 2024)
The study aims at exposing the discovery learning applied at high education. The study applies descriptive qualitative design applying phenomenology. The subjects in this study were 3 lecturers of a private university in Yogyakarta, Indonesia. The data were gained from interviews and documentations. The data are analyzed using triangulation involving data reduction, data display, and drawing conclusion. The analysis results show that there are benefits and challenges of discovery learning applied in higher education. In conclusion, discovery learning has been one of alternative teaching ways in higher education. Keywords: discovery learning, English language teaching, higher education